2008
DOI: 10.1001/jama.2008.886
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Risk of Type 2 Diabetes

Abstract: In most populations studied, birth weight was inversely related to type 2 diabetes risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
321
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(346 citation statements)
references
References 75 publications
25
321
0
Order By: Relevance
“…Although the evidence for a similar positive impact on neurocognitive outcomes is relatively sparse, the potential for such long‐term benefits on height and neurocognition makes the promotion of infancy weight gain an appealing policy. On the other hand, insulin resistance is higher in SGA catch‐up children than in the general population and this finding is supported by consistent evidence on the association between low birthweight and type 2 diabetes 7.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although the evidence for a similar positive impact on neurocognitive outcomes is relatively sparse, the potential for such long‐term benefits on height and neurocognition makes the promotion of infancy weight gain an appealing policy. On the other hand, insulin resistance is higher in SGA catch‐up children than in the general population and this finding is supported by consistent evidence on the association between low birthweight and type 2 diabetes 7.…”
Section: Discussionmentioning
confidence: 52%
“…However, if the actual conditions do not match the ones predicted, the adaptation can have an adverse impact on long‐term health, leading to disease 6. Associations have been widely observed between low birthweight and later noncommunicable diseases, such as type 2 diabetes 7. Evidence from animal and human models has led to the suggestion that those associations with low birthweight are mediated, in part, by rapid postnatal weight gain and catch‐up growth leading to excessive adiposity 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Low birth weight is a well‐established risk factor for cardiovascular disease,1 type 2 diabetes mellitus,2 and hypertension,3 as well as several other known atrial fibrillation (AF) risk factors, such as pulmonary function 4, 5. There are 3 previous studies that report on associations between self‐reported birth weight and incident AF, with divergent results.…”
Section: Introductionmentioning
confidence: 99%
“…One very large study used data from more than 230,000 individuals in the UK Biobank (Tyrrell et al 2013), finding that paternal diabetes at conception predicts the risk of diabetes in offspring, and further, that birthweight at least partly mediates this association; low birthweight is in and of itself an established predictor of type 2 diabetes in later life (Whincup et al 2008). Studies of the Guangzhou birth cohort of China found that paternal BMI positively correlated with fetal growth in males, as well as with cortisol levels in newborns (Chen et al 2012).…”
Section: Epidemiological Observations Implicate Fathers In Children'smentioning
confidence: 99%